Star polylactide and its stereocomplex blends with enhanced heat stability triggered by microwave heating for degradable packaging - Wilairat Supmak; Suthawan Buchatip; Mantana Opaprakasit; Atitsa Petchsuk; Pakorn Opaprakasit (Scientific Reports)
Abstract Poly(D-lactide) with a star-shaped structure (starPDLA) has been synthesized and blended with commercial linear PLLA (l-PLLA) to enhance processability, thermal stability, and mechanical properties via stereocomplexation and incorporation of covalent junctions with compact structure from the star-shaped polymer. The blends, with a starPDLA content of 0.1 and 0.2, showed increased elongation at break by 35–43 times and toughness by 40–47 times compared to l-PLLA, with a slight reduction in tensile strength and modulus. The blends were fabricated into packaging trays by film extrusion and thermoforming. The DSC, FTIR, and XRD results indicated that the tray products initially possessed low crystallinity due to the high cooling rate of the fabrication process. Upon microwave heating, the electromagnetic field interacts with polar functional groups of the chains, generating heat at a slightly higher temperature than the Tg of the materials and triggering chain rearrangement to form favorable stereocomplex structures, enhancing their heat resistance and shape stability. These are suitable for warming foods with low water or oil content, e.g., frozen cooked rice or popcorn. The degradable packaging products have a high potential as a choice for microwavable single-use packaging for foods with low water or oil content.